Cognitive and brain correlates of acquired number-colour synaesthetic-like associations. (10th February 2022) - Arend, Isabel; Yuen, Kenneth; Ashkenazi, Sarit; Henik, Avishai
Abstract: Synaesthesia is a condition in which one sensory dimension triggers another sensation. The exact contribution of genetic and environmental factors in synaesthesia is not yet fully understood. Most synaesthesia phenotypes involve associations in which the synaesthetic inducer constitutes some form of linguistic/conceptual information acquired during the course of development (e.g., digits, letters, and names of months). To study the role of learning in synaesthesia, we induced synaesthesia by training and examined the behavioural and brain correlates of number-colour associations. We took advantage of the well-known behavioural and neural signature of numbers and used number symbols as inducers. Short (2 weeks) and long (4 weeks) training protocols were conducted with two different groups. Task-related BOLD response was acquired while participants performed Stroop tasks requiring naming colours while ignoring the stimuli (i.e., number symbols, dots, words). If the arbitrary association involving number-colour is automatic, the irrelevant dimension (i.e., numbers) would interfere with the colour response. In addition, if number-colour associations are transferred to linguistic and non-symbolic representations, the passive viewing of stimuli (i.e., words and dots) would disrupt colour naming. Behavioural findings showed automatic associations as both training protocols elicited reliable congruency effects for all stimulus dimensions. Congruency effects following both training protocols produced reliable brain activations in various cortical sites involved in number and in cognitive control. The behavioural and brain patterns reported here support the role of learning in the brain correlates of developmental synaesthesia and provide the first evidence that automatic associations involving different magnitude dimensions can be acquired. Highlights: In synaesthesia colours and numbers are automatically associated. The role of learning in synaesthesia is still poorly understood. We examined learning by training number-colour associations in non-synaesthetes. Stroop-like tasks showed automaticity involving colours and different magnitudes. Brain patterns resembled those reported in genuine synaesthesia.